Solid polymer electrolyte, preparation method and sodium ion battery
By using a solid polymer electrolyte composed of polymer matrix, sodium difluoroxalate borate and carbonate, the safety hazards and insufficient cycle stability of organic electrolytes in sodium ion batteries are solved, and efficient sodium ion battery performance is achieved, especially the stability under high temperature and low temperature conditions.
Patent Information
- Application Number
- CN202411663535.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-04
AI Technical Summary
The use of organic electrolytes in existing sodium ion batteries poses safety risks, and the cycle stability and high-temperature and low-temperature performance of solid-state batteries are insufficient.
The solid polymer electrolyte consisting of a polymer matrix, sodium difluoroxalate borate and carbonate are used to improve the ionic conductivity and electrochemical window of the electrolyte by controlling the mass-volume ratio of the material and the preparation process.
The high cycle stability and excellent high-temperature and low-temperature performance of solid-state sodium ion batteries were achieved, especially the stable cycle of 6000 cycles at 3C ratio, with a capacity retention rate of 72.1%, and performed well at high temperatures 60℃ and low temperatures -20℃.
Smart Images

Figure CN119560627A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a solid polymer electrolyte, a preparation method and a sodium ion battery, and in particular to a solid polymer electrolyte with an ultra-long life, a preparation method and a sodium ion battery, and belongs to the field of solid electrolytes. Background Art
[0002] As an emerging energy storage technology, sodium-ion batteries (NIBs) have received widespread attention in recent years. Their main advantages are that sodium resources are abundant, cost-effective, and their working principles are similar to those of lithium-ion batteries, which makes sodium-ion batteries have great application potential in large-scale energy storage. However, sodium-ion batteries use organic electrolytes as ion transmission media, which poses huge safety risks. Using solid electrolytes to replace electrolytes to assemble sodium solid-state batteries has become the current mainstream solution strategy.
[0003] Solid polymer electrolytes are key components in sodium solid-state batteries. They are usually composed of a polymer matrix, sodium salts and plasticizers. The main advantages of this electrolyte are its high thermal stability, good mechanical properties and excellent safety performance. Compared with traditional liquid electrolytes, solid polymer electrolytes can inhibit the growth of sodium dendrites, and have excellent mechanical strength and flexibility, thereby improving the safety of the battery. In addition, solid polymer electrolytes are also cheap, environmentally friendly, easy to encapsulate and non-leaking, making it possible to achieve next-generation batteries with high energy density and high safety.
[0004] Among the many components in solid polymer electrolytes, sodium salts play a vital role. Choosing different sodium salts will affect the electrochemical window, room temperature ionic conductivity and interface stability of the battery. Sodium salts with high dissociation degree can improve the ionic conductivity of the electrolyte, thereby improving the overall performance of the battery. In addition, the electrochemical window of sodium salts directly affects the operating voltage range of the battery and is a key factor affecting the safety and cycle life of the electrolyte and battery. A wide electrochemical window can ensure that the electrolyte will not decompose during the charge and discharge process, which is conducive to stabilizing the interface between the electrode and the electrolyte and achieving stable operation of the battery system. Summary of the invention
[0005] In view of the deficiencies of the prior art, one of the objects of the present invention is to provide a solid polymer electrolyte with excellent cycle stability; a second object of the present invention is to provide a method for preparing a solid polymer electrolyte; a third object of the present invention is to provide a sodium ion battery.
[0006] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0007] A solid polymer electrolyte comprises a polymer matrix, sodium difluorooxalatoborate and carbonate, wherein the carbonate is propylene carbonate and / or ethylene carbonate, and the mass volume ratio of the polymer matrix, sodium difluorooxalatoborate and carbonate is 1g:0.1-0.5g:0.6-2ml.
[0008] Furthermore, the mass volume ratio of the polymer matrix, sodium difluorooxalatoborate and carbonate is 1 g: 0.2-0.4 g: 0.7-1.5 ml.
[0009] Furthermore, the mass volume ratio of the polymer matrix, sodium difluorooxalatoborate and carbonate is 1 g: 0.25-0.35 g: 0.8-1.2 ml.
[0010] Furthermore, the polymer matrix is poly(vinylidene fluoride-hexafluoropropylene).
[0011] Furthermore, the weight average molecular weight of poly(vinylidene fluoride-hexafluoropropylene) is 200,000-600,000, further 300,000-500,000, further 350,000-450,000, and preferably 320,000-420,000.
[0012] Furthermore, the solid polymer electrolyte is in a film shape, and the thickness of the solid polymer electrolyte is 200-1000 μm, preferably 400-800 μm.
[0013] Based on the same inventive concept, the present invention also provides: a method for preparing the solid polymer electrolyte as described above, comprising the following steps:
[0014] S1. In an atmosphere protection environment, a polymer matrix, sodium difluorooxalatoborate, a carbonate and an organic solvent are uniformly mixed in a ratio of 1 g: 0.1-0.5 g: 0.5-1.5 ml: 8-12 ml to obtain an electrolyte slurry;
[0015] S2. After the electrolyte slurry is scraped onto the template, the template is placed in an oven for drying, and then demoulding is performed to obtain a film-like solid polymer electrolyte.
[0016] Further, in S2, the mixture is mixed uniformly at 35-55° C.; preferably, the organic solvent is acetone.
[0017] Furthermore, in S2, after the electrolyte slurry is scraped onto the template, it is placed in an oven together with the template, left to dry for 4-8 minutes, and then vacuum dried for 11-15 minutes. Preferably, the drying temperature is room temperature.
[0018] Furthermore, in S2, a scraper is used for coating, and the template is a glass plate.
[0019] Based on the same inventive concept, the present invention also provides: a sodium ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is the solid polymer electrolyte as described above or a solid polymer electrolyte prepared by the preparation method as described above.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The solid polymer electrolyte of the present invention has high ionic conductivity and can be used in sodium solid-state batteries to show excellent cycle stability, especially at high rate conditions. The prepared sodium solid-state battery has a capacity retention rate of 72.1% after 6,000 stable cycles at a rate of 3C. In addition, the prepared sodium solid-state battery has a capacity retention rate of 91.8% after 250 cycles of charge and discharge at a rate of 1C at a high temperature of 60°C. The charge and discharge test can also be carried out normally at a low temperature of -20°C, and both have excellent cycle stability.
[0022] (2) The present invention selects suitable small molecule carbonate and sodium salt additives and controls their addition ratio, which can effectively improve the ionic conductivity and electrochemical window of the solid polymer electrolyte and improve the cycle performance of the resulting sodium ion battery.
[0023] (3) The solid polymer electrolyte preparation method of the present invention has a simple process. By static drying and vacuum drying, the obtained solid polymer electrolyte can be effectively guaranteed to be complete and stable in morphology while effectively improving efficiency, which is conducive to promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is the AC impedance test spectrum of the solid polymer electrolyte of Examples 1-4 of the present invention at room temperature.
[0025] Figure 2 It is a charge and discharge cycle performance diagram of the NVP@C||Na full battery of Examples 1-4 of the present invention at 3C.
[0026] Figure 3 It is a graph showing the changes in cycle time and voltage of the Na||Na symmetric batteries of Example 1 of the present invention and Comparative Examples 2-4.
[0027] Figure 4 This is the AC impedance spectrum of Comparative Example 5.
[0028] Figure 5 This is the AC impedance spectrum of Comparative Example 6.
[0029] Figure 6 These are photographs of the solid polymer electrolyte of Comparative Example 7 before drying (a) and the solid polymer electrolyte after direct vacuum drying for 15 minutes (b).
[0030] Figure 7 These are photographs of the solid polymer electrolyte (a) of Comparative Example 8 before drying and the solid polymer electrolyte (b) after being allowed to dry for 3 minutes and then vacuum dried for 12 minutes.
[0031] Figure 8 The solid polymer electrolyte (a) of Example 1 before drying and the solid polymer electrolyte (b) after being allowed to dry for 5 minutes and then vacuum dried for 10 minutes.
[0032] Fig. 9 This is a graph of the full battery of Example 1 subjected to charge and discharge cycle testing at a high temperature of 60°C at a rate of 1C.
[0033] Fig.10 This is a graph of the full battery of Example 1 undergoing charge and discharge cycle testing at a low temperature of -20°C at a rate of 0.2C.
[0034] Fig.11 These are photographs of the solid polymer electrolyte (a) before drying and the solid polymer electrolyte (b) after being allowed to dry for 5 minutes and then vacuum dried for 10 minutes in Example 8. DETAILED DESCRIPTION
[0035] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0036] Example 1
[0037] The preparation method of the solid polymer electrolyte of this embodiment is as follows:
[0038] Step 1: Weigh 1 g of poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP, weight average molecular weight of 400,000), 0.2 g of sodium difluorooxalatoborate (NaDFOB), 1 ml of propylene carbonate (PC), and 10 ml of acetone (AC), place the above raw materials in a serum bottle in an atmosphere protection environment, and stir at a temperature of 45° C. and a rotation speed of 800 r / min for 24 hours to obtain an electrolyte slurry;
[0039] Step 2: The obtained electrolyte slurry was coated on a glass plate using a 1000 μm scraper, and then placed in an oven at room temperature for 5 min and then vacuumed for 10 min to remove the organic solvent. The mold was then released to obtain a self-supporting solid polymer electrolyte (with a thickness of about 600 μm).
[0040] Based on the obtained solid polymer electrolyte, a stainless steel / polymer electrolyte / stainless steel button cell was assembled, and an electrochemical workstation was used to perform an electrochemical impedance spectroscopy (EIS) test and a linear sweep voltammetry test. The room temperature ionic conductivity and electrochemical window (LSV) data of the polymer electrolyte were calculated and the results are shown in Table 1.
[0041] Based on the obtained solid polymer electrolyte, a Na||Na symmetric battery was assembled in the order of positive electrode shell, sodium sheet, solid polymer electrolyte, sodium sheet, and negative electrode shell to test the cycle performance. 2 The energy density and 0.1mA / cm 2 The deposition-stripping test was carried out at room temperature with a current density of , and the deposition-stripping cycle time when the polarization voltage was within 0.6 V was counted. The statistical results of the data of this embodiment are recorded in Table 1.
[0042] Based on the obtained solid polymer electrolyte, the NVP@C||Na full battery was assembled in the order of positive electrode shell, positive electrode sheet, polymer electrolyte membrane, sodium sheet (negative electrode), steel sheet, and negative electrode shell, and the cycle performance test was carried out. The specific operation is: within the electrochemical window range of 2.0-3.8V, the charge and discharge cycle test was carried out at room temperature with a rate of 3C, and the number of cycles with a capacity retention rate of 80% was counted. The statistical results of the data in this example are recorded in Table 1.
[0043] Among them, the production process of the positive electrode sheet is as follows: the positive electrode material (NVP), conductive agent (SP) and binder (PVDF) are mixed evenly in a mass ratio of 8:1:1, coated on the carbon-coated aluminum current collector, placed in a vacuum oven at 80°C for vacuum drying for 12 hours, taken out, and cut with a cutter with a diameter of 12 mm to obtain the positive electrode sheet.
[0044] Example 2
[0045] Example 1 was repeated, except that the amount of sodium difluorooxalatoborate (NaDFOB) added was 0.1 g.
[0046] Example 3
[0047] Example 1 was repeated, except that the amount of sodium difluorooxalatoborate (NaDFOB) added was 0.3 g.
[0048] Example 4
[0049] Example 1 was repeated, except that the amount of sodium difluorooxalatoborate (NaDFOB) added was 0.4 g.
[0050] Comparative Example 1
[0051] Example 1 was repeated, except that the amount of propylene carbonate (PC) added was 0.5 ml.
[0052] The results showed that during the evaporation of the solvent in step 2, the film slowly curled up and gradually hardened, making it impossible to assemble the battery.
[0053] Example 5
[0054] Example 1 was repeated, except that the amount of propylene carbonate (PC) added was 0.8 ml.
[0055] Example 6
[0056] Example 1 was repeated, except that the content of propylene carbonate (PC) was 1.5 ml.
[0057] Example 7
[0058] Example 1 was repeated, except that the amount of propylene carbonate (PC) added was 2.0 ml.
[0059] Comparative Example 2
[0060] Example 1 was repeated except that the sodium salt was replaced with sodium hexafluorophosphate (NaPF 6 )0.2g.
[0061] Comparative Example 3
[0062] Example 1 was repeated except that the sodium salt was replaced with sodium perchlorate (NaClO 4 )0.2g.
[0063] Comparative Example 4
[0064] Example 1 was repeated, except that the sodium salt was replaced with 0.2 g of sodium bis(trifluoromethylsulfonyl)imide (NaTFSI).
[0065] Comparative Example 5
[0066] Example 1 was repeated, except that PC was replaced by DMC.
[0067] As a result, the AC impedance spectrum test found that the internal impedance of the electrolyte membrane was large and could not meet the basic requirements of the electrolyte membrane. The impedance spectrum is attached. Figure 4 .
[0068] Comparative Example 6
[0069] Example 1 is repeated, with the only difference being that the PC is replaced with a DME.
[0070] As a result, the AC impedance spectrum test found that the internal impedance of the electrolyte membrane was large and could not meet the basic requirements of the electrolyte membrane. The impedance spectrum is attached. Figure 5 .
[0071] Example 8
[0072] Example 1 was repeated, except that PC was replaced with EC (ethylene carbonate).
[0073] It can be seen that in the solid polymer electrolyte system of the present invention, ideal performance can be obtained by adding PC.
[0074] Table 1
[0075]
[0076]
[0077] See also Figure 1 As the amount of NaDFOB added increases, the ionic conductivity of the solid polymer electrolyte membrane at room temperature continues to increase. The possible reason is that the increase in the sodium salt content increases the number of mobile sodium ions inside the polymer electrolyte membrane, thereby improving the room temperature ionic conductivity of the electrolyte membrane. However, its electrochemical window, deposition and stripping time, 3C cycle number and other aspects are not positively correlated with the amount of NaDFOB added.
[0078] See also Figure 2 , with the increase of NaDFOB addition, the cycle stability of the whole battery at 3C rate is significantly enhanced. When NaDFOB accounts for 20wt% of the polymer matrix PVDF-HFP, the battery can stably cycle 6000 cycles with a capacity retention rate of 72.1%. At this time, further increasing the amount of NaDFOB, the cycle stability of the whole battery shows a significant downward trend. The possible reason is that since some NaDFOB cannot be dissolved, tiny particles agglomerate, and the transmission of ions in the polymer electrolyte is hindered. In addition, the mechanical properties of the electrolyte membrane will also be weakened, resulting in a decrease in the anti-dendrite ability, which leads to a significant downward trend in the cycle stability of the battery.
[0079] See also Figure 3 , compared with NaPF 6 、NaClO 4 The solid polymer electrolyte with NaDFOB as the main sodium source has excellent compatibility with sodium metal, and its symmetric battery can achieve a high performance at 0.1 mAh / cm 2 The energy density and 0.1mA / cm 2 The deposition and stripping was stable at a current density of at least 800 h, and the DFOB - The anions form an excellent SEI film at the interface, which significantly improves the ion transport at the interface and reduces the interface polarization voltage from the original 0.43V to 0.18V.
[0080] Comparative Example 7
[0081] Example 1 was repeated, except that in step 2, the organic solvent was removed by direct vacuuming in an oven at room temperature for 15 min (ie, without standing treatment).
[0082] Comparative Example 8
[0083] Example 1 was repeated, except that in step 2, the organic solvent was removed by placing the mixture in an oven at room temperature for 3 min and then applying vacuum for 12 min.
[0084] from Figures 6 to 8 and Fig.11 It can be seen that when drying, the surface of the polymer-based solid electrolyte membrane that has not been left to stand has many unevenly distributed water droplet-shaped ripples and partial salt precipitation. The possible reason is that when vacuuming, the wind force is too strong, the solvent evaporates unevenly, or the solvent evaporates too quickly, resulting in bubble-like defects or corrugated defects. After standing for 3 minutes and then vacuum drying, the flatness of the surface of the polymer-based solid electrolyte membrane is significantly improved, but there are still large ripples. The possible reason is that the standing drying time is not long enough, and the thickness of the semi-gel film formed on the membrane surface is too small, which is difficult to resist the evaporation of the remaining solvent. The adverse effect on the film morphology caused by the vacuum drying for 5 minutes; after standing for 5 minutes and then vacuum drying, the surface flatness of the obtained polymer-based solid electrolyte membrane is good, and there is no water droplet pattern. The possible reason is that part of the organic solvent has achieved uniform volatilization and formed a relatively thick film in a semi-gel state on the membrane surface, which can effectively reduce the influence of the airflow on the membrane morphology during subsequent vacuuming, so that the organic solvent inside the membrane can be discharged more evenly during vacuuming, and the residual solvent is avoided. The surface morphology of the membrane is significantly affected when volatilizing, and the membrane surface is avoided from generating ripples or water droplet-shaped patterns, thereby obtaining a higher quality polymer-based solid electrolyte. At the same time, the method is simple and fast, and can effectively shorten the process time. It can be seen that the above-mentioned drying process of the present invention can not only ensure the flatness of the morphology of the final polymer-based solid electrolyte membrane, but also improve the drying efficiency, which is helpful for industrial application.
[0085] Depend on Fig. 9 It can be seen that under the synergistic effect of carbonate and sodium difluorooxalatoborate, the NVP@C||Na full battery obtained in Example 1 still has excellent electrochemical stability at a high temperature of 60°C. The possible reason is that the introduction of PC improves the high temperature resistance of the solid polymer electrolyte, and the dense SEI film formed by NaDFOB at the interface significantly improves the electrochemical performance of the battery at high temperature; similarly, from Fig.10 It can also be seen that the NVP@C||Na full battery obtained in Example 1 also has good cycle stability at -20°C. After 250 cycles at a rate of 0.2C, the capacity is maintained at 73.7%, showing good low-temperature cycle performance.
[0086] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.
Claims
1. A solid polymer electrolyte, characterized in that The invention comprises a polymer matrix, sodium difluorooxalatoborate and carbonate, wherein the carbonate is propylene carbonate and / or ethylene carbonate, and the mass volume ratio of the polymer matrix, sodium difluorooxalatoborate and carbonate is 1g:0.1-0.5g:0.6-2ml.
2. The solid polymer electrolyte according to claim 1, characterized in that The mass volume ratio of the polymer matrix, sodium difluorooxalatoborate and carbonate is 1g: 0.2-0.4g: 0.7-1.5ml.
3. The solid polymer electrolyte according to claim 1, characterized in that The mass volume ratio of the polymer matrix, sodium difluorooxalatoborate and carbonate is 1g: 0.25-0.35g: 0.8-1.2ml.
4. The solid polymer electrolyte according to any one of claims 1 to 3, characterized in that The polymer matrix is poly(vinylidene fluoride-hexafluoropropylene); preferably, the weight average molecular weight of poly(vinylidene fluoride-hexafluoropropylene) is 200,000-600,000, further 300,000-500,000, further 350,000-450,000, and more preferably 320,000-420,000.
5. The solid polymer electrolyte according to any one of claims 1 to 3, characterized in that: The solid polymer electrolyte is in a film shape, and the thickness of the solid polymer electrolyte is 200-1000 μm, preferably 400-800 μm.
6. The method for preparing a solid polymer electrolyte according to any one of claims 1 to 5, characterized in that: The steps include: S1. In an atmosphere protection environment, a polymer matrix, sodium difluorooxalatoborate, a carbonate and an organic solvent are uniformly mixed in a ratio of 1 g: 0.1-0.5 g: 0.5-1.5 ml: 8-12 ml to obtain an electrolyte slurry; S2. After the electrolyte slurry is scraped onto the template, the template is placed in an oven for drying, and then demoulding is performed to obtain a film-like solid polymer electrolyte.
7. The preparation method according to claim 6, characterized in that: In S2, the mixture is mixed uniformly at 35-55° C.; preferably, the organic solvent is acetone.
8. The preparation method according to claim 6, characterized in that: In S2, after the electrolyte slurry is scraped onto the template, it is placed in an oven together with the template, left to dry for 4-8 minutes, and then vacuum dried for 11-15 minutes. Preferably, the drying temperature is room temperature.
9. The preparation method according to claim 6, characterized in that: In S2, a scraper is used for scraping, and the template is a glass plate.
10. A sodium ion battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The electrolyte is a solid polymer electrolyte as described in any one of claims 1 to 5 or a solid polymer electrolyte prepared by the preparation method as described in any one of claims 6 to 9.